THE USAGE OF DERIVATIVES IN FINANCIAL RISK MANAGEMENT BY COMPANIES IN BOSNIA AND HERZEGOVINA - Emira Kozarević; Izudin Kešetović; Meldina Kokorović Jukan; Beriz Čivić (Economic Review)
The main objective of this paper is to determine the scope of the use of derivatives by companies in BiH for specific purposes of financial risk management. The aim is to provide a comparative analysis with companies from Slovenia and Croatia in order to determine if companies in BiH use the hedging instruments appropriately, and to suggest possible improvements of their practices for managing financial risks. The basic goals of the paper are to explore if companies in BiH use derivatives for risk management purposes to the same extent as Slovenian and Croatian companies and to determine if BiH companies properly hedge their financial risks. The paper also aims to give suggestions to BiH companies for improvements of their risk management practices in order to ensure more efficient and effective financial risk hedging by using derivatives, primarily available through banks on BiH financial markets.